Pendidikan Karakter melalui Metafora dan Nilai Budaya Sastra Lisan Dolabololo - Ati, Sarmina; Gay, Masayu (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this research is to analyze character education of forms, types, and meanings of metaphors and their relevance to cultural values ​​in the Ternate community. This study qualitative approach by utilizing content analysis methods and integrating them with the theory of metaphor analysis by Knowles and Moon. The research was conducted in Ternate Island District. The research subjects are the indigenous people of Ternate who are in the Ternate Island District, and the traditional holders of the Ternate Sultanate Palace. The data in this study is in the form of traditional Dolabololo expressions obtained from interviews and written documentation. The stages of analyzing the data are through data reduction, data presentation, and data verification stages. The value of cultural character education contained in the ontological metaphor is the teaching to always tell the truth and describe the culture of mutual respect and respect that the people of Ternate have.